SILENCE USED IN ACEHNESE - Asrah Raihana; Asmaul Husna; Fadhila Hayani; Putri Permata Sari Samosir (Universitas Islam Sumatera Utara (UISU), 2018)
Language is very important in society. It is used to communicate with other people in everyday life. The understanding of language in communication becomes very important according to the main purpose of the use of the language itself which can be associated as a medium for delivering a message or information. As a tool of communication, language is not only conveyed orally, but also in silence. Every word has a meaning, silence also delivers a message and it has interpretations in meaning and purpose. The use of silence can also be found among Acehnese while having communication. Silence is a complex phenomenon and embodies diverse concepts. In most usages of the word, silence has some degrees of relativity and often refers to states, which may not be silent at all. While some situations require the use of silence in some contexts, the other researches were found that using of silence for unnecessary situation. The objective of this study is to analyze how silence used in Acehnese. What the meaning and function of silence used by Acehnese are. The method was Acehnese’s conversations. From the data analysis, it showed that the respondents showed that silence found in conversation between Acehnese mostly used as a variety of politeness, to hide feeling ashamed, guilty, and angry. Besides that, it also showed a respect to elders, express agreement and disagreement. The silence used is also an influence of a custom in each culture descriptive qualitative. The source of the data was taken by recording of. In Acehnese culture, silence mostly used for showing polite behavior and respect toward people based on the context of the communication in social interaction.